Open-Label Pilot Study to Compare the Safety and Immunogenicity of Pentavalent Rotavirus Vaccine (RV5) Administered on an Early Alternative Dosing Schedule with Those of RV5 Administered on the Recommended Standard Schedule. (3rd March 2017) - Saleh, Ezzeldin; Eichner, Brian; Clark, Douglas W; Gagliano, Martha E; Troutman, James M; Harrington, Lynn; McNeal, Monica; Clements, Dennis
Abstract: This study compares the safety and immunogenicity of pentavalent rotavirus vaccine (RV5) administered on an alternative schedule (initiated at 2–5 weeks of age) with those of RV5 administered on the recommended standard schedule. Our findings support the future conduct of larger clinical trials to confirm the safety and efficacy of rotavirus vaccination in the neonatal period.